The multidrug-resistant Candida auris, Candida haemulonii complex and phylogenetic related species: Insights into antifungal resistance mechanisms - Lívia S. Ramos; Pedro F. Barbosa; Carolline M.A. Lorentino; Joice C. Lima; Antonio L. Braga; Raquel V. Lima; Lucas Giovanini; Ana Lúcia Casemiro; Nahyara L.M. Siqueira; Stefanie C. Costa; Célia F. Rodrigues; Maryam Roudbary; et al. (Current Research in Microbial Sciences)
The rise of multidrug-resistant (MDR) fungal pathogens poses a serious global threat to human health. Of particular concern are Candida auris, the Candida haemulonii complex (which includes C. haemulonii sensu stricto, C. duobushaemulonii and C. haemulonii var. vulnera), and phylogenetically related species, including C. pseudohaemulonii and C. vulturna. These emerging, widespread, and opportunistic pathogens have drawn significant attention due to their reduced susceptibility to commonly used antifungal agents, particularly azoles and polyenes, and, in some cases, therapy-induced resistance to echinocandins. Notably, C. auris is classified in the critical priority group on the World Health Organization's fungal priority pathogens list, which highlights fungal species capable of causing systemic infections with significant mortality and morbidity risks as well as the challenges posed by their MDR profiles, limited treatment and management options. The mechanisms underlying antifungal resistance within these emerging fungal species is still being explored, but some advances have been achieved in the past few years. In this review, we compile current literature on the distribution of susceptible and resistant clinical strains of C. auris, C. haemulonii complex, C. pseudohaemulonii and C. vulturna across various antifungal classes, including azoles (fluconazole, voriconazole, itraconazole), polyenes (amphotericin B), echinocandins (caspofungin, micafungin, anidulafungin), and pyrimidine analogues (flucytosine). We also outline the main antifungal resistance mechanisms identified in planktonic cells of these yeast species. Finally, we explore the impact of biofilm formation, a classical virulence attribute of fungi, on antifungal resistance, highlighting the resistance mechanisms associated with this complex microbial structure that have been uncovered to date.